GAMBARAN PENURUNAN INDEKS PLAK GIGI SETELAH MENGGUNAKAN PASTA GIGI DAUN SIRIH DAN PASTA GIGI XYLITOL (LITERATURE REVIEW) (Jurnal Terapi Gigi dan Mulut, 2022)
Plaque is a soft deposit that is firmly attached to the surface of the tooth, consisting of microorganisms that multiply in an intercellular matrix when a person neglects the hygiene of his teeth and mouth. Mechanical plaque control efforts can be done by brushing teeth while chemical control is using antibacterial chemicals such as toothpaste, and mouthwash. There are various kinds of enhancing substances in toothpaste circulating in the market today such as betel leaves and xylitol. This research is entitled Overview of Decreasing Dental Plaque Index after using betel leaf toothpaste and xylitol toothpaste. The method in finding article data sources is carried out through the Pubmed, Science Direct and Google Scholar eresources databases (2015-2022) to collect relevant articles published in English and Indonesian. Terms and keywords related to Betel leaf herbal toothpaste, xylitol toothpaste, dental plaque index in the search of related subjects. Inclusion study design uses Experimental True, Experimental Quasy, and Cross sectional. Based on the results of a literature review from 7 journals consisting of the characteristics of 5 journals of the type of betel leaf herbal toothpaste and 2 xylitol toothpastes, it can be concluded that xylitol toothpaste is more effective in lowering plaque index and improving tooth and oral hygiene.